NEW DATA REGARDING THE CONDITIONS FOR THE SYNTHESIS OF SOLID SOLUTIONS OF PHOSPHATE HYDRATES WITH THE MAXIMUM AREA OF HOMOGENEITY - Антрапцева, Надія; Терещенко, Юлія; Житнецький, Ігор; Біла, Галина (Modern engineering and innovative technologies, 2023)
The conditions for obtaining a solid solution of hydrated zinc and magnesium phosphates of the general formula Zn3-хMgx(PO4)2·4H2O with the maximum range of homogeneity, which is, have been determined. The influence of various precipitants on th